Obesity-Induced Changes in Bone Marrow Homeostasis - Benova, Andrea; Tencerova, Michaela (Frontiers in Endocrinology, 2020)
Obesity is characterized by a low-grade inflammation, which is accompanied with increased accumulation of immune cells in peripheral tissues including adipose tissue, skeletal muscle, liver or pancreas impairing their primary metabolic functions in regulation of glucose homeostasis. Obesity has also shown to have a detrimental effect on bone homeostasis by skewing bone marrow and hematopoietic stem cells differentiation and thus impairing bone integrity and immune cell properties. The origin of immune cells arises in bone marrow, which has been shown to be affected with obesogenic condition by increased cellularity and shifting differentiation and function of hematopoietic and bone marrow skeletal stem cells in favor of myeloid progenitors and increased bone marrow adiposity. These obesity-induced changes in bone marrow microenvironment lead to a dramatic bone marrow remodeling and compromising immune cell functions, which in turn affects systemic inflammatory condition and regulation of a whole-body metabolism. However, there is limited information on inflammatory secretory factors creating bone marrow microenvironment and how they are changed in metabolic complications. This review will summarize recent findings on inflammatory and cellular changes in bone marrow in relation to obesity and further discuss whether dietary intervention or physical activity may bring beneficial effects on bone marrow microenvironment and whole-body metabolism.